Journal: 100 Years / The Engineering And Mining Journal New York August 10, 1907 Ground Breaking In The Joplin District Q786 Holes Are Drilled With Air Drills And Squibbed Before Charging. About 1 Pound Of Dynamite Is Required Per Ton Of Rock Broken - Doss Brittain (International Society of Explosives Engineers, 2008)
The term ground breaking is taken to include the process of so loosening the ground as to enable it to be readily loaded into buckets or cars and hoisted from the shaft or drift. In the Joplin district are encountered two varieties of ground, the hard and the soft. Hard ground consists of massively bedded rock requiring heavy blasting to loosen it. Such ground is to be found throughout the district in the same localities as the soft ground but more extensively, even to the exclusion of the appearance of soft ground in the sheet formation in the vicinity of Webb City. The Yellow Dog Mine at Webb City and the Grace mine on the Granby land at Joplin furnish well known examples of hardground mining which has become the most extensive in the district.